A systematic literature review on self-presentation strategies in dating app profiles - Duan, Xiaomeng; Mahbob, Maizatul Haizan (Edelweiss Applied Science and Technology, 2025)
With the growing global popularity of dating applications, users’ self-presentation strategies within their profiles have increasingly become a key topic of scholarly interest. Guided by Page, et al. [1] this systematic literature review retrieved relevant studies from two major databases—Scopus and Web of Science (WoS)—focusing on English-language publications from 2020 to 2024. A total of 39 representative studies were ultimately included for analysis. This review identified three overarching themes: content dimensions, platform influences, and socio-cultural and identity-related factors, which were further broken down into nine subthemes. The findings suggest that users’ self-presentation on dating apps is primarily shaped by visually driven cues aimed at attractiveness, strategic textual disclosure, and platform-specific affordances. Additionally, gender role expectations and cultural backgrounds play a significant role in shaping users’ self-presentation strategies. The key contribution of this review lies in its systematic synthesis of fragmented and interdisciplinary research in the field. It highlights the lack of attention to issues such as algorithmic mediation, cross-cultural variation in self-presentation, and the behaviors of older user groups. By outlining potential directions for future research, this review offers a structured analytical perspective on self-presentation in digital dating environments and provides a valuable foundation for future empirical studies and platform design practices.